Evaluation of Seismic Vulnerability Index and Soil Classification in Sleman Regency Based on Microtremor Analysis and the HVSR Method - Fadlika Widyantari, Elsa; Aryono Adhi, Mochamad; Rahma, Ilqia; Budi Wibowo, Nugroho; Mustami' Limayukha, Desi; El Farsiyyi, Bilqis; Sofyana Ulya, Rahmania (Rekayasa, 2023)
Kalasan District and Ngemplak District, located in Sleman Regency, Yogyakarta, are areas with significant seismic risk due to the subduction of the Indo-Australian and Eurasian plates south of Java Island. To support disaster mitigation and land-use planning, it is essential to understand the local geological structure and soil dynamic response. This study aims to evaluate the seismic vulnerability and soil classification using the Horizontal to Vertical Spectral Ratio (HVSR) method and Rayleigh wave ellipticity inversion modeling. Microtremor measurements were conducted at 27 points distributed across both districts. The HVSR method was used to obtain the dominant frequency and amplification values, while the ellipticity inversion of Rayleigh waves was employed to estimate the shear-wave velocity profile and calculate Vs₃₀ values. The results show that the dominant frequency ranges from 0.713 Hz to 18.006 Hz, amplification values range from 0.569 to 4.193, and the seismic vulnerability index ranges from 0.010 to 12.060. Based on these parameters, Sleman Regency is generally categorized as having low to moderate seismic damage potential due to the relatively low amplification and vulnerability index. The Vs₃₀ values indicate a variation in soil site classes, namely medium-density soil (SD) and very dense soil (SC). These findings provide essential data for seismic microzonation, contributing to more resilient urban development strategies.